2021
DOI: 10.1155/2021/6829806
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Phytomediated Zinc Oxide Nanoparticles on Growth and Oxidative Stress Response of In Vitro Raised Shoots of Ochradenus arabicus

Abstract: Biogenic nanoparticles have potential roles in the growth and development of plants and animals as they are ecofriendly and free of chemical contaminants. In this study, we assessed the effects of phytomediated zinc oxide nanoparticles (ZnONPs) on shoot growth, biochemical markers, and antioxidant system response in Ochradenus arabicus, which is a medicinal plant. The shoot length and fresh and dry weights were found to be higher in groups with 5 and 10 mg/L ZnONPs than in the control. At high concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…The contents of proline and TBARS were increased in the leaves of E. macrochaetus, which was observed in all treatments with ZnO-NP application. Our result is confirmed according to Al-Qurainy et al [28], as their application of ZnO-NPs on tissue-culture-raised shoots of Ochradenus arabicus enhanced the levels of both proline and TBARS. Similarly, ZnO-NP treatment on Momordica charantia enhanced proline content and up-regulated antioxidant enzyme activity [60].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The contents of proline and TBARS were increased in the leaves of E. macrochaetus, which was observed in all treatments with ZnO-NP application. Our result is confirmed according to Al-Qurainy et al [28], as their application of ZnO-NPs on tissue-culture-raised shoots of Ochradenus arabicus enhanced the levels of both proline and TBARS. Similarly, ZnO-NP treatment on Momordica charantia enhanced proline content and up-regulated antioxidant enzyme activity [60].…”
Section: Discussionsupporting
confidence: 88%
“…The result of Karimi et al [67] showed that low concentrations of NPs have been found to promote plant growth and the production of secondary metabolites. In another study, ZnO-NP treatment enhanced the polyphenolic content in plants [28,48,60]. Similarly, the polyphenolic compounds (lignans and neolignans) were enhanced in cell suspension cultures of Linum usitatissimum under ZnO-NP treatments [29].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In addition, at optimum concentrations, it provides a favorable response against abiotic stresses in field plants [20][21][22][23][24][25][26][27][28]. ZnO improves plant tolerance against abiotic stress in various plants by causing in vitro shoot proliferation and boosting various secondary metabolites in Ochradenus arabicus [29]. Positive effects of foliar spraying of ZnO NPs were recorded on plant growth [30,31] in many crop plants under stress, such as eggplant, tomato, brassica, and foxtail millet [26,[32][33][34][35][36] and also studied by Ahmed et al [37], compared with Zn nutrients in tomato plants in detail.…”
Section: Introductionmentioning
confidence: 99%